Cevap :
f(x+2)-f(x+1)=x
X=0 için
f(2)-f(1)=0
X=1 için
f(3)-f(2)=1
X=2 için
f(4)-f(3)=2
.
.
.
.
X=11 için
f(13)-f(12)=11
Çapraz olanlar birbirini götürür geriye
f(13)-f(1)=66 kalır soru bize f(1) in 1 olduğunu söylemiş
X-1=66
X=67 olur Yani f(13)=67
İnşallah doğrudur :)
X=0 için
f(2)-f(1)=0
X=1 için
f(3)-f(2)=1
X=2 için
f(4)-f(3)=2
.
.
.
.
X=11 için
f(13)-f(12)=11
Çapraz olanlar birbirini götürür geriye
f(13)-f(1)=66 kalır soru bize f(1) in 1 olduğunu söylemiş
X-1=66
X=67 olur Yani f(13)=67
İnşallah doğrudur :)